2014
DOI: 10.1111/zoj.12155
|View full text |Cite
|
Sign up to set email alerts
|

New proviverrines (Hyaenodontida) from the early Eocene of Europe; phylogeny and ecological evolution of the Proviverrinae

Abstract: We describe six proviverrine species from the Early Eocene of France. Three species are new: Minimovellentodon russelli sp. nov. from Mutigny [mammal palaeogene (MP)8 + 9], Boritia duffaudi sp. nov. from La Borie (MP8 + 9), and Leonhardtina godinoti sp. nov. from Grauves (MP10). We describe new specimens and propose new generic combinations for three species from MP10: Protoproviverra palaeonictides, Matthodon menui, and Oxyaenoides lindgreni. We also propose a new generic combination for the primitive Eoprovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(80 citation statements)
references
References 52 publications
(160 reference statements)
3
77
0
Order By: Relevance
“…Tinerhodon was considered by McKenna & Bell (1997) to be part of Cimolestidae, but Gheerbrant et al (2006) disputed its cimolestid affinities, suggesting that it was a basal hyaenodont based on comparisons to Boualitomus . Subsequent studies (Solé, 2013; Solé, Falconnet & Yves, 2014; Solé et al, 2014; Solé et al, 2015) found Tinerhodon to be the sister group of Hyaenodonta while Rana et al (2015) found Tinerhodon to be the sister taxon of Lahimia + Boualitomus , a clade that occupied multiple positions in their analysis. None of the analyses performed here recover Lahimia and Boualitomus in such a basal position, and none place Tinerhodon as the sister taxon to Hyaenodonta to the exclusion of Altacreodus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tinerhodon was considered by McKenna & Bell (1997) to be part of Cimolestidae, but Gheerbrant et al (2006) disputed its cimolestid affinities, suggesting that it was a basal hyaenodont based on comparisons to Boualitomus . Subsequent studies (Solé, 2013; Solé, Falconnet & Yves, 2014; Solé et al, 2014; Solé et al, 2015) found Tinerhodon to be the sister group of Hyaenodonta while Rana et al (2015) found Tinerhodon to be the sister taxon of Lahimia + Boualitomus , a clade that occupied multiple positions in their analysis. None of the analyses performed here recover Lahimia and Boualitomus in such a basal position, and none place Tinerhodon as the sister taxon to Hyaenodonta to the exclusion of Altacreodus.…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship between Hyaenodontinae and some European proviverrines was first demonstrated by Polly (1996) when Eurotherium was resolved as the sister taxon to Propterodon + Hyaenodon . Contra Solé (2013) and Solé, Falconnet & Yves (2014) who found Proviverra and Eurotherium were part of a monophyletic Proviverrinae, Polly (1996) proposed Proviverra as the sister taxon to all more deeply nested hyaenodonts and Eurotherium as closely related to Propterodon and Hyaenodon . Rana et al (2015) were the first to include Propterodon and Hyaenodon in a phylogenetic analysis since Polly (1996); they also included many more proviverrines than Polly (1996) and found a monophyletic, entirely European Proviverrinae as the sister clade to Hyaenodontinae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations